南极普里兹湾及邻近海域初级生产力的时空变异 - 邱雨生; 黄奕普; 刘广山; 陈敏 (厦门大学, 2004)
在南大洋海冰区碳循环的研究中,初级生产力是最重要的基础数据之一.本文就中国南极科考第15、16航次的观测结果,着重讨论普里兹湾及邻近海域初级生产力(PP)的时空变异.第15、16航次生产力的平均测值分别为394.1和271.6mgC·m-2·d-1,第16航次略低于第15航次.PP的空间分布呈湾内高,湾外低(陆坡、深海区最低)的特征.光合速率的垂直分布呈现次表层极大值型、随深度递减型和极小、极大迭加型3种分布特征,其分布受光照主控.初级生产力在短至1昼夜长达10年的时间尺度内均有显著的变化,初级生产力测值的年际变化最大达2.4倍. 【英文摘要】 In present study, primary productivity (PP) and its spatial and temporal variations in Prydz Bay and its adjacent sea area were studied during the 15th and 16th CHINARE cruises.The results showed that the average primary productivity of the 15th cruise was 394.1 mgC·m~(-2)·d~(-1), slightly higher than that of 16th cruise (271.6 mgC·m~(-2)·d~(-1)).While the higher levels within the bay,PP was lower for outside of the bay,with the lowest in slope and deep water regions.The profiles of photosynthetic rates (PR. 国家自然科学基金(49836010);; 南极"十五"计划(2001DIA50040)资助